Little Friends - Shemilt, Jane (London : Penguin Books, 2020)
Their children are friends first. They hit it off immediately, as kids do. And so the parents are forced to get to know each other. Three wildly different couples. Three marriages, floundering. The couples are so busy watching each other that they forget to watch their children. Until tragedy strikes.
Keywords: Children -- Fiction; Parents -- Fiction; Interpersonal relations -- Fiction; Thrillers (Fiction)